IMPLEMENTATION OF REFLECTIVE PEDAGOGY TO PROMOTE PROSPECTIVE MATHEMATICS TEACHERS ENTHUSIASM - Margaretha Madha Melissa (IJIET (International Journal of Indonesian Education and Teaching), 2018)
In this study described the implementation of Reflective Pedagogy in psychology of learning course to promote prospective mathematics teachers enthusiasm. To obtain data learning enthusiasm, researcher gives questionnaire of learning enthusiasm to prospective mathematics teachers and also asks them to do reflection. The result of questionnaire of learning enthusiasm is described quantitatively and supported by data of reflection. The result of learning enthusiasm questionnaire shows that the average of prospective mathematics teachers enthusiasm in cycle 2 is higher than cycle 1, that is 78,19 76,15 and the average is in good category. It is also supported by the results of student reflection which states that students learning enthusiasm is improved after they learn psychology of learning course based on Reflective Pedagogy. So, the implementation of Reflective Pedagogy in psychology of learning can foster prospective mathematics teachers enthusiasm.DOI: https://doi.org/10.24071/ijiet.2018.020104